Study on spa typologies, spatial organisation and social interaction in accordance with Islamic built environment attributes - Othman, Rashidi; Mohd Noor, Nur Fadhlina; Ahmad, Nurliyana; Manan, Nurwina Aishah; Hashim, Khairusy Syakirin Has-Yun; Mahamod, Lukman Hakim; Ahmad Fadzillah, Nurrulhidayah (Kulliyyah of Architecture, International Islamic University Malaysia, 2018)
Spas have become increasingly popular and have emerged as important profit centers for hotels. However, the uniqueness of this market has been largely overlooked in terms of Shari’ah compliance to better cater to Muslim needs. This study repositions spa typologies, their spatial organization and social interaction in the context of Islamic built environment. A survey was administered at four case different spas in Kuala Lumpur and Selangor to identify the dimensions of a Muslim-friendly spa. Cluster analysis was then applied to classify spa premises into different groups based on the typologies, services and spatial organization. The analysis was performed according to the groups to determine Muslim-friendly elements. Based on the findings, a Shari’ah-compliant considers security, privacy, and segregation of genders in its design. This research provides further information on the understanding, practice, features, and requirements of Muslim-friendly spas which will help to boost Malaysia’s potential to become a prominent destination for Islamic or Shari’ah-compliant tourism.